MODERASI BERAGAMA DALAM PERSPEKTIF HADIS NABI: ANALISIS HADIS YASSIRU WA LA TU’ASSIRU DALAM MEMBINA TOLERANSI DAN PERSAUDARAAAN - Muhammad Fauzi Batubara; Muhammad Fawwaz; Mohd Nazri Bin Johari (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines religious moderation from the perspective of the Prophet's hadith as a response to the growing problems of extremism, intolerance, and social division in plural societies. The discussion focuses on the hadith yassiru wa la tu'assiru, which emphasizes ease in religious practice and preaching. This research applies a qualitative approach based on library research. The data are analyzed through hadith takhrij, sanad and matan criticism, and hadith commentary, supported by mutaba'ah and syawahid. The findings show that the hadith yassiru wa la tu'assiru is authentic and strengthened by several chains of transmission, making it a valid normative foundation for developing a moderate religious attitude. Its core content affirms the principles of taysir, tasamuh, and a non-burdensome method of da'wah. The hadith also contains a psychological dimension that emphasizes the importance of calmness and a non-repelling approach in conveying Islamic teachings. In the contemporary context, these values are highly relevant for reducing extremist attitudes, strengthening tolerance, maintaining brotherhood, and building a peaceful, inclusive, and civilized social life. The implementation of these principles is expected to make a meaningful contribution toward constructing a harmonious society in accordance with the primary objectives of Islamic law.